MICROBIOLOGICAL PROPERTIES OF COW MANURE VERMICOMPOST IN CONTROLLING CLUBROOT DISEASE - Riani, Esti
Clubroot disease, caused by pathogen Plasmodiophora brassicae, is a serious threat to the cultivation of family Brassicaceae plants worldwide. The increasing use of chemicals to control this disease has caused various negative and detrimental effects. Vermicompost as an environmentally friendly organic material was reported to significantly control clubroot disease. However, no studies have evaluated the suppressive properties of vermicompost against clubroot. This study aims to examine the microbiological properties of vermicompost and its relation to the suppressive properties of vermicompost against clubroot. Vermicompost made from cow manure is obtained from Kampung Pasir Angling, Suntenjaya Village, West Bandung Regency. The microbiological properties were observed including diversity, evenness, abundance, dominance, chitinase activity, and the effectiveness of potential microbes in controlling clubroot disease individually. The chitinase activity test was carried out on colloidal chitin medium for bacteria and Colloidal Chitin Bromocresol purple (CCBp) medium for fungi. The clubroot control test was conducted using a completely randomized design method (CRD) in a screen house. The results showed that cow manure vermicompost contained 21 bacterial isolates with an abundance of 2.09 x 107 CFU/g and was dominated by isolates B19 (37%) and B25 (25%). The vermicompost bacterial community has moderate diversity (2.05) and high evenness (0.67). Meanwhile, the number of fungal vermicompost isolates was 20 isolates with an abundance of 1.11 x 106 CFU/g and was dominated by isolates F7 (53%) and F3 (24%). The fungal vermicompost community has moderate diversity (1.58) and moderate evenness (0.53). The chitinase-producing microbes were from the bacterial group, namely isolates B3 (12.08%), B6 (125.55%), B19 (93.55%), and B25 (113.51%). Meanwhile, no chitinase activity was observed from the dominant fungal isolates. Isolates B19 and B25 were selected as potential isolates based on the highest chitinolytic index and abundance for the clubroot control test individually. The results of the control test against clubroot showed that isolate B25 was able to reduce the incidence of clubroot from 6.25% to 3.12%. Based on the 16S rRNA gene analysis, isolate B25 is Streptomyces coelicoflavus with 100% similarity.